Bacteriophage-based therapy in cystic fibrosis-associated Pseudomonas aeruginosa infections: rationale and current status - Hraiech S; Brégeon F; Rolain JM (Dove Medical Press, 2015)
Sami Hraiech,1,2 Fabienne Brégeon,1,3 Jean-Marc Rolain1 1Institut Hospitalo-Universitaire Méditerranée Infection, URMITE CNRS IRD INSERM UMR 7278, 2Réanimation Médicale – Détresses Respiratoires et Infections Sévères, APHM, CHU Nord, 3Service d’Explorations Fonctionnelles Respiratoires, APHM, CHU Nord, Marseille, France Abstract: Pulmonary infections involving Pseudomonas aeruginosa are among the leading causes of the deterioration of the respiratory status of cystic fibrosis (CF) patients. The emergence of multidrug-resistant strains in such populations, favored by iterative antibiotic cures, has led to the urgent need for new therapies. Among them, bacteriophage-based therapies deserve a focus. One century of empiric use in the ex-USSR countries suggests that bacteriophages may have beneficial effects against a large range of bacterial infections. Interest in bacteriophages has recently renewed in Western countries, and the in vitro data available suggest that bacteriophage-based therapy may be of significant interest for the treatment of pulmonary infections in CF patients. Although the clinical data concerning this specific population are relatively scarce, the beginning of the first large randomized study evaluating bacteriophage-based therapy in burn infections suggests that the time has come to assess the effectiveness of this new therapy in CF P. aeruginosa pneumonia. Consequently, the aim of this review is, after a brief history, to summarize the evidence concerning bacteriophage efficacy against P. aeruginosa and, more specifically, the in vitro studies, animal models, and clinical trials targeting CF. Keywords: pneumonia, pulmonary infection, bacterial infection, multidrug resistance